OPTIMALISASI PERAN KOMANDO RAYON MILITER DALAM KEGIATAN KOMUNIKASI SOSIAL (KOMSOS) UNTUK PEMBINAAN KETAHANAN WILAYAH (Studi di Koramil 0502-06/Kelapa Gading, Jakarta Utara) - , ENDRO JATMOKO ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The national defense as one functions of state government which is an effort to create and to achieve the unificationof national defense goals setting forth in the Preamble of the 1945 Constitution by protecting the whole nation and the homeland of Indonesia, to promote general welfare, intellectual life of the nation and participate in implementing the world order based on freedom, keeping peace and social justice. The changing role of Indonesian National Armyâs, essential threats, and regional autonomy needan adjustment of the Armyâs role in particularly Military Sub-District Command as the leader in maintaining regional resilience and the integrity of the Republic of Indonesia has to be optimized its role and organization. The purpose of this study is to recognize the real situation and condition in the region and to comprehend about (1) The actualization Military Sub-District Command inmaintaing territorial atsocial communication activities (2) The empowerment of Military Sub-District Command officers, community partnershipin social communication (3) To optimize the Military Sub-District Command role in social communication for the regional resilience. The study uses qualitative methods mainly by collecting and analyzing written texts. Besides, its providing the overall situation which is being studied. The research data isobtained from primary data and secondary data.The Primary data as aliterature data invarious forms,such as books, internet sites and other literature sources, the primary data come from some interviews with connecting officials and community at the research locust. The result of study shows that: (1) The Description of current conditions is a real picture aboutthe Military Sub-District Command roleâs condition as the spearhead of Area Commandandthe Territorial Commando still facing softwareand application tasks problems and hesitate to carry out its duties because of Indonesian National Army role transition. (2) The Military Sub- District Commandrole is still necessary at the activityof social communication, it can be achieved if components of the apparatus all together having a sense of strong nationalis mand patriotism as well as budgeting support that fit to the needs and demands of the stateâs ability will be creating the efforts and balance in order to deal with the dynamics that occur in society. (3) In creating the regional resilience, Military Sub-District Commandcarries out the optimal role and make continuousef forts to gain a support for cooperation with Sub district Leaders Conference and connected institutions along with the local community by maintaining Social Communication, Struggle and Resistance of Indonesian National Armyâs servicein order to get emphaty and achieved the military people unity.